2019
DOI: 10.18203/2320-6012.ijrms20191311
|View full text |Cite
|
Sign up to set email alerts
|

Variations, relations and clinical significance of carotid arterial system in anterior neck: a cadaveric study

Abstract: Background: The common carotid, internal and external carotid arteries and their branches serve as major source of blood supply in head-neck region of human and are often encountered during numerous surgical and clinical interventions of neck.Methods: We dissected and examined both sides of neck in 49 well embalmed cadavers (98 sides). We recorded the following anatomical parameters of carotid arterial system-level of bifurcation, the relation between internal and external carotid arteries, branching pattern o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Various scholars have conveyed the cases of thyrolingual trunk originating from the CCA (2). Ghosh et al reported an extremely rare variation where STA originated from the internal carotid artery near the CCA bifurcation level (10). Thwin S et al noticed a common linguofacial stem in their studies (11).…”
Section: Origin Of Superior Thyroid Artery From Different Source Of V...mentioning
confidence: 99%
“…Various scholars have conveyed the cases of thyrolingual trunk originating from the CCA (2). Ghosh et al reported an extremely rare variation where STA originated from the internal carotid artery near the CCA bifurcation level (10). Thwin S et al noticed a common linguofacial stem in their studies (11).…”
Section: Origin Of Superior Thyroid Artery From Different Source Of V...mentioning
confidence: 99%
“…2 Variations in the right external carotid artery originating from superior thyroid arteries are frequently documented in classical anatomical, surgical and radiological textbooks. [4][5] Ample knowledge about variations in arterial supply of superior thyroid artery is required prior to formulating planned neck surgeries This study aims to find out the prevalence of right superior thyroid artery originating from the right external carotid artery in cadavers of a medical college in Nepal.…”
Section: Introductionmentioning
confidence: 99%